The financialization of healthcare - Norberto Montani Martins; Carlos Ocké-Reis (Revue de la Régulation)
In contemporary capitalism, finance has extended its reach to encompass a growing array of economic sectors traditionally associated with public provisioning or social policy, with healthcare emerging as a prominent domain where fictitious capital has flourished. Financialization exerts a direct influence on the delivery of public health services while also reshaping the behavior and operations of private healthcare providers and health insurance firms. This paper aims to characterize the process of financialization of healthcare in Brazil by analyzing the behavior of firms in the private health insurance market from 2007 to 2019. These firms provide healthcare coverage alongside the functioning of the Unified Health System (SUS), constituting an avenue for the accumulation of capital. The paper analyzes how the strategies for managing assets, liabilities, and the equity of leader firms operating in the market of private healthcare plans firms, as expressed by the movements recorded in their balance sheets, inform us on their process of financialization. A set of financialization indexes is developed, addressing: (i) asset financialization; (ii) liability financialization; and (iii) the maximization of shareholder value. Economic-financial data and financial statements made available by the Brazilian Regulatory Agency for Private Health Insurance (ANS) are used to build such indexes. The results show a greater engagement of leader firms in the allocation of their resources in financial assets, but the weight of financial gains in total profits is small. Regarding indebtedness, results do not show an increase in leverage and financial burden, and does not confirm the hypothesis of increased susceptibility to creditor influence. Finally, changes in the equity structure and initial public offerings suggest a greater alignment of management practices with the standards of corporate governance established in capital markets. We conclude that those firms are increasingly serving as platforms for the financial accumulation of other economic agents and set a research agenda on this topic.